2011
DOI: 10.1039/c1ob05058c
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic and biological studies of discorhabdins and related compounds

Abstract: Various analogues of the marine alkaloids, discorhabdins, have been synthesized. The strategy contains spirocyclization with phenyliodine(III) bis(trifluoroacetate) (PIFA), oxidative fragmentation of the β-amino alcohols with the hypervalent iodine reagent C(6)F(5)I(OCOCF(3))(2), the detosylation and dehydrogenation reaction of the pyrroloiminoquinone unit in the presence of a catalytic amount of NaN(3) and the bridged ether synthesis with HBr-AcOH as the key reactions. All the synthesized compounds were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 74 publications
(108 reference statements)
0
29
0
Order By: Relevance
“…Collectively these studies characterise the electrophilic reactivity of the spiro-dienone moiety of discorhabdin C, a structural feature that is known to be a factor, but not the sole determinant, for the cytotoxicity reported for this class of alkaloid [ 15 , 16 , 17 ]. To further explore the degree of essentiality of the dienone ring towards cytotoxicity, discorhabdin C was subjected to hydrogenation using Pd/C under an H 2 atmosphere for 15 min to afford, after workup, a blue-coloured product in 71% yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively these studies characterise the electrophilic reactivity of the spiro-dienone moiety of discorhabdin C, a structural feature that is known to be a factor, but not the sole determinant, for the cytotoxicity reported for this class of alkaloid [ 15 , 16 , 17 ]. To further explore the degree of essentiality of the dienone ring towards cytotoxicity, discorhabdin C was subjected to hydrogenation using Pd/C under an H 2 atmosphere for 15 min to afford, after workup, a blue-coloured product in 71% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Together these results prompted us to evaluate the antiparasitic activities of a series of discorhabdin natural products and semi-synthetic analogues that we have previously shown to exhibit modest or minimal tumour cell line cytotoxicity. Included in this study were (+)-discorhabdin B 1 , discorhabdin C 2 , 6 – 8 , 3-dihydrodiscorhabdin C 9 [ 15 ], (+)-discorhabdin D 10 , (-)-discorhabdin H 11 , (+)-discorhabdin H 2 12 [ 19 ] (-)-discorhabdin L 13 , discorhabdin Q 14 , discorhabdin U 15 , semi-synthetic dienone-phenol 16 [ 23 ] and discorhabdin B dimer 17 [ 5 , 16 ] ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NSC 668394 binding affinity (K D = 10.6± 2.9μM) in comparison to analogue 21a , which showed no binding to ezrin, suggested that the 3,5 dibromo-4-hydroxy substitution pattern on the aryl ring is important for ezrin binding. Addition of hydroxyl substituents on the aromatic group as shown for analogues 21f 21 and 21g resulted in slightly increased binding affinity to ezrin. Substitution of the bromine atoms with chlorine atoms as shown in analogue 21k also resulted in a statistically significant increase in ezrin-binding potency.…”
Section: Resultsmentioning
confidence: 93%
“…Tetraiodo-norbromohemibastadin-1 ( 4 ) was synthesized by iodination of 2 , utilizing a modified method of Wada et al [ 11 ]. Briefly, 2 (157.0 mg, 0.5 mmol) was dissolved in diluted sodium hydroxide solution (5 mL, pH 10), and H 2 O 2 (30% aqueous solution, 0.12 mL) and iodine (I 2 , 152.0 mg, 0.6 mmol) were added.…”
Section: Methodsmentioning
confidence: 99%